1979
DOI: 10.1104/pp.63.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase/Glutamine: α-Ketoglutarate Aminotransferase in Chloroplasts from the Marine Alga Caulerpa simpliciuscula

Abstract: The enzymic capacities for ammonia assimilation into amino acids have been investigated in chloroplasts from the siphonous green alga Caulerpa simpliciuscula (Turner) C. Ag. The results show that these chloroplasts differ from those of higher plants in having present simultaneously the enzymic capacities to permit assimilation of ammonia by two pathways.Glutamine synthetase (EC 6.3.1.2) activity at levels up to 4 jumoles per mg chlorophyll per hour were found in soluble extracts of the chloroplasts. Glutamine(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This may apply in the case of the alga Caulerpa sirnpliciuscula (Gayler and Morgan, 1976;McKenzie et al. 1979).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may apply in the case of the alga Caulerpa sirnpliciuscula (Gayler and Morgan, 1976;McKenzie et al. 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Thus while GDH activity might be of prime in the case of Isochrysis galbana in which senescent importance in nitrogen assimilation in organisms such cells were assayed because they exhibited greater as Caulerpa simpliciuscula (Gayler and Morgan, 1976; levels of GS activity. McKenzie et al, 1979) and in Stichococcus bacillaris (Everest and Syrett, in press), it appears to play only a secondary role in marine phytoplankton. We report here the detection of glutamine synthetase activity in a wide variety of marine phytoplankton, all exhibiting much greater apparent affinity for scavenging ammonium ions than reported for GDH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well accepted that glutamate synthase (glutamine:aketoglutarate aminotransferase; GOGAT2) catalyzes the second step of nitrogen assimilation into glutamate via glutamine in the presence of glutamine synthetase (EC 6.3.1.2) in bacteria (18,32), algae (10,14), nitrogen-fixing organisms (3,24), and higher plants (16).…”
mentioning
confidence: 99%
“…NADH-GOGAT has been found in Chlamydomonas reinhardtu by Cullimore & Sims (1981a,b) and Marquez et al (1984) and in Euglena graciLis by Miyatake & Kitaoka (1981). Since Cuhmore & Sims (1981a) found that methyl viologen-GOGAT and NADH-GOGAT in C. reinhardtii appeared to be the same isozyme, the reported in vitro GOGAT activities mediated by the artificial electron donors methyl viologen in Caulerpa simpliciuscula (McKenzie et al 1979) and benzyl viologen in Platy-monas striata (Edge & hcketts 1978) may be indicative of NADH-GOGAT in these algal species. However, Marquez et al (1984) found that methyl viologen-GOGAT could correspond to both the NADH and ferredoxin forms of the enzyme.…”
Section: Discussionmentioning
confidence: 99%